2014
DOI: 10.1021/nn405535j
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electron Transfer Properties of ZnO and TiO2 Photoanodes for Dye-Sensitized Solar Cells

Abstract: Mesoporous TiO2 nanoparticle films are used as photoanodes for high-efficiency dye-sensitized solar cells (DSCs). In spite of excellent photovoltaic power conversion efficiencies (PCEs) displayed by titanium dioxide nanoparticle structures, the transport rate of electrons is known to be low due to low electron mobility. So the alternate oxides, including ZnO, that possesses high electron mobility are being investigated as potential candidates for photoanodes. However, the PCE with ZnO is still lower than with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
181
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(187 citation statements)
references
References 70 publications
6
181
0
Order By: Relevance
“…The chemical stability of ZnO is, however, less than that of TiO 2 , which was found to be problematic in the dyeadsorption procedure. Low electron injection efficiency from excited dye molecules to ZnO is also an obstacle to obtaining high efficiency [66][67][68].…”
Section: Usage Of Zno Nanotetrapods As Photoanodic Materials In Dsscsmentioning
confidence: 99%
“…The chemical stability of ZnO is, however, less than that of TiO 2 , which was found to be problematic in the dyeadsorption procedure. Low electron injection efficiency from excited dye molecules to ZnO is also an obstacle to obtaining high efficiency [66][67][68].…”
Section: Usage Of Zno Nanotetrapods As Photoanodic Materials In Dsscsmentioning
confidence: 99%
“…Au) as the key components. The mp-TiO 2 layer in a typical dye-sensitized solar cell (DSSC) plays three major roles; provides a scaffold to increase the surface area of the absorber layer, act as a hole blocker, and transports photogenerated electron from the sensitized surface to the front contact 11 . Therefore, the active surface area which has a direct link with particle size of mesoporous material is a key parameter in DSSC 12 .…”
mentioning
confidence: 99%
“…This observation has been attributed to the higher rate of recombination in ZnO compared to TiO 2 [17]. Two different radiative recombination processes were found to be involved in the excitonic emission of ZnO-free exciton recombination (slow) and near surface exciton recombination (fast) [19].…”
Section: Photoexcitation and Charge Separationmentioning
confidence: 96%
“…Despite possessing higher electron mobility, several studies have shown that ZnO demonstrated a lower photo-conversion efficiency compared to TiO 2 [17,18]. This observation has been attributed to the higher rate of recombination in ZnO compared to TiO 2 [17].…”
Section: Photoexcitation and Charge Separationmentioning
confidence: 99%